Effect of Multi-enzymes Supplementation in Egg type Chicks Diet with Varying Protein and Energy levels During Hot-dry Summer - Dukare, S. P.; Mandal, A. B.; Rokade, J. J.; Dinani, O. P. (International Journal of Bio-resource and Stress Management, 2017)
An experiment was conducted to evaluate the effects of dietary inclusion of (multi-enzymes) maxi-zyme at different energy and protein level on performance of egg-type chicks during hot-dry summer. After feeding a standard diet from 0-21d of age, the chicks were randomly distributed into four dietary treatment groups viz., T1 with high energy 2800 kcal ME kg-1 and high protein 18.0% (HEHP), T2 HEHP diet with maxi-zyme 0.025% and T3 with low energy 2700 kcal ME kg-1 low protein 17.34% (LELP) and T4 with LELP diet with maxi-zyme 0.025%. Each treatment is with fifty birds divided in five replicated of ten birds each. Experiment was carried out during hot-dry summer (April-May, 28.0±0.12 oC to 35.25±0.37 oC and RH %: 68.95±0.90 to 79.15±0.61). Production performance, immune organ weight, blood biochemical and intestinal morphometry were measured at 42nd and 63rd day post hatch. Body weight gain, Feed intake and FCR improved significantly (P<0.05) in HEHP+maxi-zyme group. H:L ratio significantly (p<0.05) reduced in maxi-zyme supplemented group at 42nd as well as 63rd day of age. Immune organ like thymus, spleen and bursa had significantly (p<0.05) higher weight in maxi-zyme supplemented group. Total protein (p<0.001), SGOT (p<0.001), SGPT (p<0.001), creatinine (p<0.05) were significantly improved while cholesterol, uric acid & ALP was significantly (p<0.001) reduced in maxi-zyme supplemented diets. Villus height & crypt depth improved significantly (p<0.001) in maxi-zyme supplemented group at 42nd as well as 63rd day of age. Thus, it was concluded that high-energy (2800 kcal ME kg-1) and high protein (18% CP) diet was beneficial for egg type starting chicks during dry summer. Moreover, the inclusion of maxi-zyme @ 0.025% gave further advantage to improve performance and reduce thermal stress.